Analysis of Influence of Ultra-High Pressure Water Jet Cutting Pressure Sequence on Pressure Relief and Reflection Improvement of Coal Seam - Shoulong Ma (Advances in Civil Engineering)
In order to explore the pressure relief effect of the two combined pressure relief and antireflection technologies of ultra-high pressure water jet cutting before pressure and pressure before cutting, theoretical analysis, numerical simulation, and field test were used to study the main control factors of the combined high-pressure water jet slit cutting and fracturing antireflection technology. This paper introduces the combined technology of ultra-high pressure hydraulic fracturing, and analyses the mechanism of pressure relief and transparency enhancement of the combination of cutting before pressure and pressure relief after cutting. The results show that the starting pressure of the coal seam with ultra-high pressure water jet cutting and pressure relief is 13 MPa, the influence radius of hydraulic fracturing is 45–55 m, the starting pressure of the coal seam with pressure cutting and pressure relief is 16 MPa, and the influence radius of hydraulic fracturing is 35–45 m. Compared with pressure cutting combined pressure relief and permeability enhancement technology, cutting pressure relief and permeability enhancement technology can improve the permeability of coal seams more evenly and effectively, and reduce the stress of coal seams near the hole. The ultra-high pressure cutting and pressure combined technology can make the pressure relief of coal body uniform and sufficient, and the overall permeability coefficient of the coal body is greatly improved. The drilling purity is 2.3 times of the extraction purity of the ordinary single hole drilling, and the extraction influence range is increased, and the extraction effect is significantly improved. At the same time, the stress of coal body is reduced after slitting, and the starting pressure of hydraulic fracturing is reduced. The research results provide a scientific basis for the coal seam pressure relief and permeability enhancement under similar conditions in the mining area and have a broad application prospect.